SOSIALISASI PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH BERBASIS MARKETPLACE DI DESA DIBAL KABUPATEN BOYOLALI - Arif Yulianto; Meydiasya Huda Aqilla; Muhammad Aziiz Al Rasyid; Jilang Rahmadania (Universitas Sahid Surakarta, 2022)
Abstract: The lack of knowledge of the MSME community regarding the use of technology in marketing makes the marketing of MSME products less than optimal, especially in the midst of a pandemic condition like today. Therefore, this community service is carried out with the aim of introducing the use of internet technology in marketing MSME products. Community service activities (PKM) aim to provide education about the importance of developing market place-based micro, small and medium enterprises, so that MSME products can be sold to the maximum during the pandemic. this covid. The activity was carried out in Dusun Wangkis rt 02 rw 07 Dibal, Ngemplak Boyolali. Benefits of the activity: (a) application of digital marketing (shopee), (b) utilization of household waste in the form of plastic, cardboard, straws, coffee packs. The positive impact of community service is the introduction of the importance of social media and digital marketing for sales. Keywords: Training, digital marketing, entrepreneurs, household waste, Dibal